2014
DOI: 10.1007/s00253-014-5766-8
|View full text |Cite
|
Sign up to set email alerts
|

PQQ-dependent methanol dehydrogenases: rare-earth elements make a difference

Abstract: Methanol dehydrogenase (MDH) catalyzes the first step in methanol use by methylotrophic bacteria and the second step in methane conversion by methanotrophs. Gram-negative bacteria possess an MDH with pyrroloquinoline quinone (PQQ) as its catalytic center. This MDH belongs to the broad class of eight-bladed β propeller quinoproteins, which comprise a range of other alcohol and aldehyde dehydrogenases. A well-investigated MDH is the heterotetrameric MxaFI-MDH, which is composed of two large catalytic subunits (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
449
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(468 citation statements)
references
References 135 publications
14
449
0
5
Order By: Relevance
“…Previous work showed that the lanthanide-dependent XoxF-type MDH enzymes are more widespread than the classical MxaFtype MDH enzymes in known methylotrophs and other organisms (40)(41)(42). In line with previous findings with other methanotrophs (26,27), we provide evidence that in pure culture in the presence of lanthanum the XoxF-type (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous work showed that the lanthanide-dependent XoxF-type MDH enzymes are more widespread than the classical MxaFtype MDH enzymes in known methylotrophs and other organisms (40)(41)(42). In line with previous findings with other methanotrophs (26,27), we provide evidence that in pure culture in the presence of lanthanum the XoxF-type (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…In the methanotroph Methylacidiphilum fumariolicum SolV, the affinity for methanol of XoxF-type MDH was much higher than reported for other MDHs, with a K m of 0.8 μM (40). If the same is true in M. tundripaludum 31/32, the lower affinity of the MxaF-type MDH could result in methanol excretion.…”
Section: Discussionmentioning
confidence: 75%
“…Also present are genes for the lanthanide-dependent (xoxF) methanol dehydrogenase involved in methanol oxidation to formaldehyde, NAD(P)-dependent methylene-H 4 MPT dehydrogenase (mtd) involved in formaldehyde oxidation to formate, and formate dehydrogenase (fdh) for formate oxidation to CO 2 . The presence of XoxF type methanol dehydrogenases, but absence of the calcium-dependent MxaF type, has also been reported for pelagic non-methanotrophic methylotrophs with relatively small genomes (Giovannoni et al, 2008) and is consistent with recent studies suggesting the prevalence of XoxF compared to MxaF in natural systems (Keltjens et al, 2014;Ramachandran and Walsh, 2015).…”
Section: Recovery Of the Genome Of An Opu3-like Methanotrophic Denitrsupporting
confidence: 75%
“…In addition, they use the rare coenzyme pyrroloquinoline quinone (PQQ). The xoxF gene is clustered with genes for the periplasmic protein XoxJ and the cytochrome c homolog XoxG, a genome context also known from other xoxF homologs (28). These data strongly suggest that Ca.…”
Section: Resultsmentioning
confidence: 52%
“…This finding is typical for methylotrophic organisms, such as Methylobacterium extorquens (27). Intrigued by this result, we constructed a phylogenetic tree of the candidate MDH proteins together with known MDHs classified by Keltjens et al (28). Both Ca.…”
Section: Resultsmentioning
confidence: 99%